Melanocortin 1 Receptor Targeted Imaging of Melanoma With Gold Nanocages and Positron Emission Tomography - Yongfeng Zhao PhD; Bo Pang PhD; Lisa Detering MS; Hannah Luehmann MS; Miaoxin Yang PhD; Kvar Black PhD; Deborah Sultan BS; Younan Xia PhD; Yongjian Liu PhD (Molecular Imaging)
Purpose: Melanoma is a lethal skin cancer with unmet clinical needs for targeted imaging and therapy. Nanoscale materials conjugated with targeting components have shown great potential to improve tumor delivery efficiency while minimizing undesirable side effects in vivo. Herein, we proposed to develop targeted nanoparticles for melanoma theranostics. Method: In this work, gold nanocages (AuNCs) were conjugated with α-melanocyte-stimulating hormone (α-MSH) peptide and radiolabeled with 64 Cu for melanocortin 1 receptor-(MC1R) targeted positron emission tomography (PET) in a mouse B16/F10 melanoma model. Results: Their controlled synthesis and surface chemistry enabled well-defined structure and radiolabeling efficiency. In vivo pharmacokinetic evaluation demonstrated comparable organ distribution between the targeted and nontargeted AuNCs. However, micro-PET/computed tomography (CT) imaging demonstrated specific and improved tumor accumulation via MC1R-mediated delivery. By increasing the coverage density of α-MSH peptide on AuNCs, the tumor delivery efficiency was improved. Conclusion: The controlled synthesis, sensitive PET imaging, and optimal tumor targeting suggested the potential of targeted AuNCs for melanoma theranostics.